2014
DOI: 10.5114/ceji.2014.42126
|View full text |Cite
|
Sign up to set email alerts
|

Primary systemic amyloidosis as a real diagnostic challenge – case study

Abstract: Primary amyloidosis (AL) is a rare variety of plasma cell dyscrasia, the diagnosis of which is often difficult to establish. Pathogenesis of amyloidosis involves extracellular deposition of insoluble protein fibrils in tissues, leading to insufficiency of affected organs. According to various sources, mean survival rate of patients with primary amyloidosis ranges from 12 to 24 months, making primary amyloidosis a disease with a very poor prognosis. Survival rate is significantly lowered in case of cardiac mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Tissue samples usually undergo red congo staining. It enables obtaining pathognomonic green birefringence of stained tissues examined under the polarization light in the tissue of the presence of amyloid deposits in the tissue specimen [22]. There is a poor interobserver reproducibility with false negatives and positives.…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Tissue samples usually undergo red congo staining. It enables obtaining pathognomonic green birefringence of stained tissues examined under the polarization light in the tissue of the presence of amyloid deposits in the tissue specimen [22]. There is a poor interobserver reproducibility with false negatives and positives.…”
Section: Ethical Approvalmentioning
confidence: 99%
“…This birefringence remains the histological gold standard for confirming the presence of amyloid in tissue [ 1 ]. The most frequent syndromes are heart failure, nephrotic syndrome, hepatomegaly and peripheral neuropathy [ 3 ]. A stepwise approach to diagnosis and staging of amyloidosis is critical and includes confirmation of amyloid deposition and identification of fibril type [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatosplenomegaly owing to amyloid infiltration is seen at presentation in 9% of AA amyloidosis patients whereas liver failure is exceptionally rare [ 7 ]. The hereditary systemic amyloidosis usually presents with renal dysfunction in their 6th or 7th decade [ 3 , 8 ]. Subsequently our constellation finding was compatible with AL amyloidosis diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it was reported that MRI may be sufficient in establishing the diagnosis without the need for brain biopsy 11. Indeed, finding a blood test for systemic amyloidosis will remain a diagnostic challenge 12…”
Section: Discussionmentioning
confidence: 99%